Women's health and corporate marketing - Hunter, Mary (Writer on women's health) (London ; New York, NY: Routledge, 2024)
This compelling collection of essays examines how historically significant marketing schemes have profoundly impacted women's health and healthcare across the world. Written by scholars and activists from a range of disciplines, including law, sociology, and the health sciences, the book spotlights a range of products that have had a damaging impact on women's health,laying barethe values and assumptions engrained within the marketing campaignsthat promoted them. Examples include the advertisement of household and personal care productsthat expose users to toxic chemicals, empowerment messaging to persuade women to use tobacco products in low- and middle-income countries, and the deceptive marketing of benzodiazepines and opioids that disproportionately impacts women and their families. A powerful critique of the unethical and paternalistic approach of some corporations, this book will find readers among students taking courses in Public Health, Allied Health, Gender Studies, Sociology, and beyond, as well as interested professionals and lay readers.
Keywords: Women -- Health and hygiene; Advertising and women; Women in marketing; Corporate image; Corporate culture; Marketing -- Moral and ethical aspects; MEDICAL / Public Health; SOCIAL SCIENCE / Women's Studies